Salmonella typhi Splenic Abscess Following Blunt Abdominal Injury: A Case Report - Sharavanan, Priyadarshini (J Clin Diagn Res, 2016)
Splenic abscess as a complication of enteric fever due to Salmonella typhi is a rare entity. Here, we are presenting a case of splenic abscess caused by Salmonella typhi with a blunt injury to the abdomen as the predisposing factor. The patient underwent total splenectomy due to failure of conservative management. Splenic abscess is a potential life threatening disease if left untreated. In spite of its rarity, Salmonella typhi has to be considered as a possible pathogen causing the disease.